2021
DOI: 10.3390/ijerph182312409
|View full text |Cite
|
Sign up to set email alerts
|

Acute-Stage Mental Health Symptoms by Natural Disaster Type: Consultations of Disaster Psychiatric Assistance Teams (DPATs) in Japan

Abstract: This study analyzed the support activities that the Disaster Psychiatric Assistance Team (DPAT) in Japan provided following four previous disasters (a volcanic eruption, a mudslide, a flood, and an earthquake) to identify links between the disaster type and the characteristics of acute stage mental disorders observed. Using Disaster Mental Health Information Support System database records of consultations with patients supported by the DPAT during the survey period from 2013 (when DPAT was launched) to 2016, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…For this study, we could only acquire a paucity of prior relevant studies and a limited amount of data about disaster psychiatry. We explored comparative and epidemiological studies on the acute phase of a disaster in the literature, but could only find two references [ 1 , 7 ]. Furthermore, this study used data from only one disaster; therefore, it is challenging to generalize and compare our findings with those from other studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this study, we could only acquire a paucity of prior relevant studies and a limited amount of data about disaster psychiatry. We explored comparative and epidemiological studies on the acute phase of a disaster in the literature, but could only find two references [ 1 , 7 ]. Furthermore, this study used data from only one disaster; therefore, it is challenging to generalize and compare our findings with those from other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The provision of mental health care from the acute phase after a disaster is critical. According to a previous epidemiological study, disaster victims tend to experience mental health symptoms such as anxiety, sleep problems, and mood and affect during this period [ 1 ]. Although mental support is required in the acute phase, a disaster is a situation that exceeds the capacity of a community to respond, and therefore requires external support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with a previous disaster psychiatry study of four natural disasters that found patients aged 20-64 years accounted for a large proportion. 19 Another study showed that older survivors were more likely to experience general psychiatric illness and posttraumatic stress disorder (PTSD) than the younger adults. 20 Likewise, large numbers of children having significant symptoms of PTSD, peri-traumatic stress, depression, and anxiety have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The need for well-trained professionals who specialize in emergencies was recognized. Consequently, Japan’s Ministry of Health, Labor and Welfare set up a formal system comprising a Disaster Psychiatric Assistance Team in 2013 [ 19 , 20 , 21 ]. However, most of the previous literature mainly focuses on the acute recovery phase and although health outcomes most frequently assessed were mental disorders, the long-term strategies have been still unclear [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%